THE OUTCOMES OF EATING DISORDER BEHAVIOR DURING PREGNANCY - Khoirinda, Ani (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2024)
Introduction – Eating disorder behavior is a serious mental illness, that is indicated by a person's eating behavior. The eating disorder has several types including anorexia nervosa, bulimia nervosa, binge eating disorder, and eating disorder not otherwise specified. Eating disorders not only occur in adolescents but can also occur in pregnant women. Eating disorders that occur during pregnancy will affect her pregnancy. Methods – The method used is a literature review. From 117 articles, 5 articles were obtained to be analyzed. Articles used for the period 2018-2023. Journal articles, published on PubMed, Europepme, Frontiers, Wiley Online Library, and Google Scholar. Articles are analyzed by looking at, the author, year, and title, researcher goals, design, and results. Results – Eating Disorder during pregnancy is fatal to the outcome of pregnancy. Small for gestational age is more common in mothers with anorexia nervosa. Large for gestational age is more common in mothers with binge eating disorder and bulimia nervosa. The supporting factors that cause eating disorders are the most important are smoking and symptoms of depression and anxiety. Discuss – Pregnant women with eating disorders (AN, BN, BED, and EDNOS) are caused by several strong factors that influence these behaviors, one of which is smoking before and during pregnancy and symptoms of anxiety and depression. Conclusion –Eating disorders in pregnancy produce a large impact on pregnancy outcomes, especially in the fetus, such as LGA, LBW, IUGR, and SGA. The impact that occurs by the fetus can also have an impact until adulthood. Therefore, mothers should be more aware of eating disorder behavior during pregnancy. Keywords: eating disorder, pregnancy, infant.